2000
DOI: 10.1093/ptj/80.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Lordosis and Pelvic Inclination in Adults With Chronic Low Back Pain

Abstract: Background and Purpose. The causes of lumbopelvic imbalances in standing have been widely accepted by physical therapists, but there is a lack of scientific evidence available to support them. We examined the association between 9 variables and pelvic inclination and lumbar lordosis during relaxed standing. Subjects. Thirty men and 30 women with chronic low back pain (CLBP) for at least 4 months were examined (mean age=54.9 years, SD=9, range=40.4–69.8). Methods. Multiple linear regression modeling was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 25 publications
7
70
2
4
Order By: Relevance
“…This was especially evident in the case of BMI. Our finding are aligned with the results of our previous study [18] and Youdas et al [20] studies, that reported higher risk of LBP in women and men with a higher BMI.…”
Section: Discussionsupporting
confidence: 93%
“…This was especially evident in the case of BMI. Our finding are aligned with the results of our previous study [18] and Youdas et al [20] studies, that reported higher risk of LBP in women and men with a higher BMI.…”
Section: Discussionsupporting
confidence: 93%
“…The relationship of gender, age and weight status with spinal curvatures has been previously studied (Murrie et al, 2003;Nourbakhsh et al, 2001;Tuzun et al, 1999;Youdas et al, 2000Youdas et al, , 1996Youdas et al, , 2006. Regarding gender, most of the studies showed that women have greater curvatures in both lumbar lordosis and thoracic kyphosis than men (Bergenudd et al, 1989;Fon et al, 1980;Milne & Lauder, 1974;Milne & Williamson, 1983;Norton et al, 2004;Youdas et al, 1996Youdas et al, , 2006, whereas other studies report that thoracic kyphosis is not influenced by gender (Boyle et al, 2002;Gelb et al, 1995;Jackson & McManus, 1994;Korovessis et al, 1998).…”
mentioning
confidence: 99%
“…It has been shown that increased lumbar lordosis and weak abdominal muscle force show a link to the contribution of LBP. 54,73 In one study, the 27 These findings support the hypothesis that the abdominals become weak during incidents of LBP and can cause increased lumbar lordosis. It has also been shown that patients with LBP have approximately 60% of absolute trunk strength compared to healthy participants.…”
Section: Back Extensors and Abdominalsmentioning
confidence: 58%
“…21 When the agonist and antagonist muscle have an imbalance in tightness or strength, pelvic obliquity and postural abnormalities occur. 9,21,22,54 The hip flexor muscle group would create an anterior tilt of the pelvis, creating more lumber lordosis, which can lead to LBP. 4,28 Throughout multiple research studies assessing the hip flexors and the relationship to LBP, no significant association between hip flexor muscle length and lumbar lordosis or LBP have been found.…”
Section: Non-specific Low Back Pain: Muscularmentioning
confidence: 99%